DETERMINANTS OF CO₂ EMISSIONS IN THE SIX LARGEST CONTRIBUTING COUNTRIES: GDP, ENERGY, POPULATION, AND RENEWABLE ENERGY - Noubel Putra Nainggolan; Eko Wahyu Nugrahadi (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2026)
This study analyzes the effects of real Gross Domestic Product (GDP), per capita energy consumption, population, and renewable energy share on CO₂ emissions in the world’s six largest emitting countries China, the United States, India, Russia, Japan, and Indonesia over the period 2015-2024. The novelty lies in integrating the Environmental Kuznets Curve, Kaya Identity, Energy Intensity Theory, Energy Transition Theory, and Sustainable Development Theory into a single post-Paris Agreement panel data model. Using balanced panel data, the study selected the Random Effect Model (REM) through Chow, Hausman, and Lagrange Multiplier tests. Results indicate that real GDP (coef. = 0.000155; p = 0.0001), per capita energy consumption (coef. = 99,418.97; p = 0.0000), and population (coef. = 4.659; p = 0.0006) have a significant positive effect on CO₂ emissions. Renewable energy has a negative but insignificant effect (coef. = -9,321,612; p = 0.6578). Jointly, the four variables explain 75.38% of CO₂ emission variation (Adj. R² = 0.7538; F = 46.171; p = 0.0000). These findings imply that emission reduction requires simultaneous structural transformation across economic growth, energy use, demographic pressure, and genuine fossil-fuel substitution, not single-variable intervention.